(untitled) (Research, Society and Development, 2024)
Objective: To identify epidemiological, tomographic, clinical and laboratory risk factors that predict mortality in patients hospitalized for COVID-19 in a private hospital in Florianópolis. Descriptors: COVID-19. Risk factors. Intensive care unit. Mortality. Methods: This is a Retrospective Cohort study. It was carried out based on patients treated for COVID-19, at Baía Sul hospital, from March to December 2020 Results: In total, 332 patients were included in the study; of these 223 (67%) were male. The mean age was 62 ± 5.32 years. There were 198 (59%) ICU admissions and 61 (18%) deaths in the population. The most prevalent tomographic pattern was ground glass with lower predominance and involvement of less than 50% of the lung. Among the previous comorbidities presented, cardiovascular disease stood out as a predictor of mortality (RR 5.308; 95% CI; 2.9-9.6). Higher levels of DDimer and Creatinine were observed in the population that died p<0.05. Conclusion: Advanced age, high levels of Creatinine and D-Dimer, and the presence of previous comorbidities, especially CVD, were the main risk factors for mortality identified.